2012
DOI: 10.1246/bcsj.20120058
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Assessment and Numerical Modeling of Photocatalytic Water Splitting toward Efficient Solar Hydrogen Production

Abstract: Photocatalytic water splitting has been studied extensively as a promising technology for scalable and cost-efficient hydrogen production using solar energy. Although overall water splitting has been achieved under visible light irradiation, significant progress in reaction efficiencies at longer wavelengths is needed to enable practical solar energy conversion. This article reports recent advancements in kinetic investigation and numerical modeling of photocatalytic water splitting to understand problems with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 38 publications
1
73
1
1
Order By: Relevance
“…Importantly, AQY generally depends on the light intensity. A number of previous studies have reported that AQY decreases with increasing light intensity because charge recombination is a second-order reaction with respect to light intensity in the high-intensity region [2]. If the dependence of AQY on photon irradiance is measured over a wide range of wavelengths using monochromatic light, the photocatalytic rates can be obtained for any light source power spectrum.…”
Section: Definition Of Photocatalytic Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, AQY generally depends on the light intensity. A number of previous studies have reported that AQY decreases with increasing light intensity because charge recombination is a second-order reaction with respect to light intensity in the high-intensity region [2]. If the dependence of AQY on photon irradiance is measured over a wide range of wavelengths using monochromatic light, the photocatalytic rates can be obtained for any light source power spectrum.…”
Section: Definition Of Photocatalytic Efficiencymentioning
confidence: 99%
“…Because the solar energy irradiating the surface of the Earth (1.3 9 10 5 TW) exceeds the current global human energy consumption (1.6 9 10 1 TW in 2010 [1]) by approximately four orders of magnitude, efficient photocatalytic solar energy conversion on a large scale should have a significant impact on energy and environmental issues as well as the economy, as described later. Figure 1 shows a simplified schematic of the reaction processes involved in overall water splitting using a single particulate photocatalyst [2]. Excited electrons and holes are generated in the bulk of the semiconductor photocatalyst particles upon band gap excitation.…”
Section: Introduction To Photocatalytic Water Splittingmentioning
confidence: 99%
“…This is a general trend for powder systems due to the requirement for sites for both reduction and oxidation and potential competitive light absorption from Co species. 25,[48][49][50] To further elucidate the state of the catalyst after pretreatment, 2 wt% CoO x /Ta 3 N 5 treated at 700 °C under NH 3 was selected for further study unless otherwise noted. The XRD patterns of Ta 3 N 5 and CoO x /Ta 3 N 5 are compared in Figure 2.…”
Section: Photocatalytic Reactionmentioning
confidence: 99%
“…20 Macroscopic design of photocatalyst particles was also proposed for efficient carrier separation. 21 …”
Section: Carrier Migration From Photocatalyst To Co-catalystmentioning
confidence: 99%